The Influence of Problem Solving Learning Models on Numerical Ability in Class V Students of 1 Way Lunik Panjang Elementary School Bandar Lampung - Haniefah, Ukhti; Asih, Nur; Suherman, Suherman (Jurnal Pendidikan Amartha, 2023)
The learning process is one of the keys to the success of education, where education is the development of potential in preparing students through learning and training activities for their future roles. In the learning process, educators are the main actors in how the learning process can be carried out, including in mathematics education in calculation material. The solution so that learning mathematics can be understood and not monotonous, for example using the problem solving learning model. The problem solving learning model will make students active by solving problems in their own way which is done together with group mates. This study aims to determine the effect of problem solving learning on the mathematical numeric abilities of class V SDN 1 Way Lunik Panjang Bandar Lampung. This study uses a type of quantitative experimental research, quasi-experimental type. The research design used was a pretest-posttest control group design. The results showed that after the researchers carried out data analysis and tested the hypothesis, namely: The use of the Problem Solving learning method had an influence on students' numerical abilities. So this shows the conclusion that there is an influence of the Problem Solving Method on the Numerical Ability of fifth grade students at SDN 1 Way Lunik Panjang Bandar Lampung.